A Kingdom in Crisis – What's All the Fuss About?. Issue 1 (2nd January 2016) - Ünaldi, Serhat
Abstract: This article reviews Andrew MacGregor Marshall's A Kingdom in Crisis: Thailand's Struggle for Democracy in the Twenty-First Century, a book on how Thailand's political challenges relate to the Thai monarchy. The review draws comparisons between the excitement surrounding the publication of the acclaimed book The King Never Smiles in 2006 and the recent reaction to the publication of A Kingdom in Crisis. It argues that the book is an important contribution because it informs a wide audience about the damaging political role of the monarchy, but it repeatedly ignores an already existing corpus of literature that deals critically with Thailand's monarchy. Moreover, its focus on the succession as the key factor in the ongoing political crisis is unnecessarily narrow and should have been complemented by an analysis of structural forces as drivers of change.